2003
DOI: 10.4321/s0210-48062003000300003
|View full text |Cite
|
Sign up to set email alerts
|

The possible macrophage role in seminal fluid

Abstract: RESUMEN "POSIBLE ROL DE LOS MACRÓFAGOS EN FLUIDO SEMINAL"Este trabajo se realizó para estudiar el rol de los macrófagos en semen y su asociación con: el porcentaje de espermatozoides con DNA nativo, morfología espermática y presencia de anticuerpos antiespermá-ticos (AAE).Se utilizó muestras de semen de 31 pacientes y se evaluaron según los criterios de la Organización Mundial de la Salud. La cromatina nuclear se estudió con Naranja de Acridina, fluorocromo que discrimina el DNA nativo, color verde, del DNA de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…This immunoglobulin is de ned as an antisperm antibody. The results from this study show that there were fewer AsAb-positive samples in the lower concentration group of macrophages (2.9% vs 9.1%), but there was no signi cant statistical difference (P > 0.05), which is different from that of related studies [7]. This was mainly due to the fact that we excluded the high-risk population of AsAb in the initial screening of the sample.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…This immunoglobulin is de ned as an antisperm antibody. The results from this study show that there were fewer AsAb-positive samples in the lower concentration group of macrophages (2.9% vs 9.1%), but there was no signi cant statistical difference (P > 0.05), which is different from that of related studies [7]. This was mainly due to the fact that we excluded the high-risk population of AsAb in the initial screening of the sample.…”
Section: Discussioncontrasting
confidence: 89%
“…There are a small number of macrophages in semen which play important roles in maintaining sperm quality [7]. They originate from the interstitial tissue of the testes and epididymis, accounting for 25% of the total testicular stromal cells [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have observed a direct relationship between the presence of macrophages and the number of sperm exhibiting denatured DNA. 25 High-load endurance training promotes the appearance of muscle injury markers along with an increased white cell count in blood. 26 During inflammation, additional circulating macrophages help testes-residing macrophages by arriving and invading the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Activated macrophages are capable of harming cells such as sperm through three principal mechanisms (Anderson, 1990; Solis et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%